PREDICTION OF ADJUSTMENT TO THE ANTARCTIC - Weybrew, Benjamin B.; Molish, H. B.; Youniss, Richard P. (1961)
Predictive validites of several psychometric tests and trait rating by teams of psychologists and psychiatrists were examined with respect to criteria of adjustment to the Antarctic during the wintering-over period of 1957. Thirty-three subjective symptoms reported monthly together with three other at itudinal criteria were intercorrelated and factor analyzed. The total N was 109. Using factor scores computed for each of the five fac ors extracted from this matrix as adjustment criteria, it was found that men with the following characteristics had the greatest adjustment potential for the Antarctic conditions: high intelligence test scores, low interest in organized sports, rated high with respect to ability to communicate, low with respect to overt hostility, high with respect to ability to cope with aggression, to have less than college education, to be single and over 25 years of age, and to have come from the southern section of the U. S. The methodological importance of the application of factor analytic techniques to repetitively collected subjective data is emphasized.